Effektivnost' deistvii v badmintone - temp ili tochnost'? - Zhbankov, O. V.; Glebovich, B. V. (Teorija i Praktika fiziceskoj Kul'tury, 1997)
The purpose of this study was elaborate the method of evaluation the rate of play and playing action's effectiveness in badminton 18 games of the elite russian badminton-players had been analysed. The rate was calculated from actual playing time and the number of strokes, realized for this time by both players. The effectiveness of playing actions of the observed player determined by theratio of succesful shuttlecock's rally to general quantity of rallies in the game. It had been concluded, that the offered method of quantitive evaluation of technical actions can be used both for the comparative analysis of the athletes' playing mastery and as the mean for improvement process's control and direction.